β-Cryptoxanthin exerts greater cardioprotective effects on cardiac ischemia-reperfusion injury than astaxanthin by attenuating mitochondrial dysfunction in mice - Pongkan W. (2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Scope: β-Cryptoxanthin and astaxanthin are antioxidant carotenoid pigments that inhibit lipid peroxidation as potently as vitamin E. We hypothesized that acute treatment with β-cryptoxanthin and astaxanthin causes similar reductions in the sizes of cardiac infarcts caused by ischemia-reperfusion (I/R) injury by attenuating oxidative stress and cardiac mitochondrial dysfunction. Methods and results: C57BL/6 mice (n = 36) were randomized to receive vehicle, β-cryptoxanthin, astaxanthin, or vitamin E at 50 mg/kg by gavage feeding prior to I/R injury. Cardiac I/R was induced by left anterior descending coronary artery ligation followed by reperfusion. All treatments significantly reduced infarct sizes by 36-57%, attenuated apoptosis and also attenuated cardiac mitochondrial dysfunction in the treated groups compared to the control group. Although astaxanthin and vitamin E exhibited similar efficacy with respect to cardioprotection, β-cryptoxanthin exhibited greater efficacy than its counterparts, as it reduced infarct sizes by 60%. β-Cryptoxanthin was more effective than astaxanthin and vitamin E because it reduced cardiac mitochondrial swelling, mitochondrial depolarization, the Bax/Bcl-2 ratio, and plasma and cardiac thiobarbituric acid reactive substances levels more significantly than its counterparts. Conclusion: Acute β-cryptoxanthin treatment exhibits greater cardioprotective efficacy against I/R injury than astaxanthin and vitamin E by reducing infarct sizes and attenuating apoptosis, oxidative stress, and mitochondrial dysfunction.